(untitled) (Phenomenology, Humanities and Sciences, 2023)
The thematization of bodily, procedural-implicit dynamics, processes, and phenomena has been approximating in the last decades phenomenology and psychoanalysis, notably phenomenological psychopathology and relational psychoanalysis. This paper aims at delineating the main thematic aspects of the current contact between these fields, focusing on their theoretic convergence and its clinic-psychotherapeutic implications. Hence, contemporary conceptions of the unconscious from both research fields are shown. One intends to highlight the limitations of the classical Freudian theory of the unconscious and especially the priority of verbal interpretation in psychotherapy. Thomas Fuchs horizontal approach to the unconscious, from the field of contemporary psychopathology, is presented. From the field of relational-psychoanalysis, the concept of implicit relational knowing as elaborated by the Boston Change Process Study Group as well as Donnel B. Stern’s concept of the unconscious as unformulated experience, are presented. As a result, it is possible to comprehend how phenomenology and psychoanalysis are currently intertwined, opening up, through a phenomenological-hermeneutical understanding of the unconscious, a privileged space to implicit-procedural aspects of relational exchanges within the clinical space.